THE CONTRIBUTION OF SHIVAMURTHYSWAMIJI IN THE STRUGGLE FOR UNIFICATION OF KARNATAKA - Basusab, Bullannavar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Though India became a free nation on August 15, 1947, the Hyderabad region was not enjoying freedom. The ruler of Hyderabad, Mir Osman Ali Khan, was reluctant to join India's union. Leaders like Veerappa Desai, YenkappaKalagudi, Giddappa Killed, Shivalingappa Holed, PanchappaShettaru, and Inamdar have been pioneers in the liberation of Hyderabad. Among the formers, M. Shivamurthappa Swami was also the one who played a key role in the unification of Karnataka. Shivamurtappa Swami brought the fragrance of freedom to his native place. He experienced the aroma of freedom till he breathed. He was the guiding force in the emancipation of Hyderabad, the unification of Karnataka, the farmers struggle, and the and the development of villages; he has rendered multiple services and brought name and fame to his state. Hyderabad has been trying to come out of being labelled as backward state.The Nanjundappa Committee had declared Koppal taluka of Koppal district as a backward region. Shivamurtappa Swami was born in Alvandi village of that-backward district. He was born 18th June,1922. Siddappa was his father, and Veeramma was his mother. Channavera Swamy and Karisidda Swamy were his brothers. Shiva Neelamma Devi, Rajamma, and Siddamma were his sisters. He was very interested in the freedom struggle in his childhood. He actively took part in the great freedom struggle. Besides India's independence struggle and Hyderabad's liberation struggle, Shivamurthy Swami was one of the prominent fighters for the unification of Karnataka. He also served as a Lok Sabha member twice. He served as the Vice President of the Nationwide Committee on Voters.